Edukasi Penggunaan Rempah Masakan Sebagai Pengobatan Alternatif pada Masyarakat di Desa Sei Limbat Tahun 2023 - Mawandha Sari Harahap; Chindy Umaya (STIKES Columbia Asia Medan, 2023)
The aim of this service activity is to provide further education to the local community regarding the use of spice plants for everyday life. Apart from that, the aim of this service activity is to encourage people in Sei Limbat Village to use spice plants more as medicine. This topic was chosen because it is a topic that is rarely discussed and rarely researched in more depth regarding spice gardens. In fact, if we look deeper, spice gardens provide many benefits for life, one of which is in the health sector. The importance of discussing this topic is so that people care more about spices than chemical medicines. The method we use is by providing education and outreach to the local community.